Navigation-guided radiofrequency ablation for osteoid osteoma in the lumbar spine with a continuous cooling system for preventing neural damage: A report of two cases - Yuichiro Ukon; Shota Takenaka; Takahiro Makino; Atsuo Shigi; Yusuke Sakai; Takashi Kaito (Interdisciplinary Neurosurgery, 2021)
Introduction: Osteoid osteoma (OO) is a benign but painful tumour that arises from osteoblasts. Spinal lesions account for 20% of OOs. Surgical excision of spinal OO has been the standard treatment when conservative therapy is not effective. However, excisional surgery can lead to spinal instability and sometimes necessitates stabilization with spinal instrumentation. Radiofrequency ablation (RFA) is an attractive option for treating spinal OO, but thermal damage to neural tissues limits its application when the OO is located adjacent to neural tissues. Case presentation: We report novel 2 cases using navigation-guided RFA for OO in the lumbar spine with a continuous cooling system for preventing neural damage. During the 5 min ablation at 90 °C, the temperature at the nerve roots adjacent to the OO was maintained at <30 °C. No neurological impairment was observed postoperatively. The symptoms caused by OO disappeared immediately after the surgery, and clinical recovery was maintained for 5 and 2 years postoperatively in Cases 1 and 2, respectively. Discussion: Direct placement of the cooling system enables both sufficient ablation and neuroprotection. The navigation system enables clinicians place the RFA probe at a precise position even in cases of OO in complex anatomical structures. To our best knowledge, this is the first report of the combined use of the navigation and cooling systems. Conclusions: This novel combinatory use of navigation-guided RFA and continuous cooling will safely expand the scope of RFA application for spinal OO by preventing neural damage and preserving spinal structure.